The clinical features and prognoses of anti-MDA5 and anti-aminoacyl-tRNA synthetase antibody double-positive dermatomyositis patients - Chen, Xixia; Zhang, Lu; Jin, Qiwen; Lu, Xin; Lei, Jieping; Peng, Qinglin; Wang, Guochun; Ge, Yongpeng (Frontiers in Immunology, 2022)
Objective To explore the clinical features and prognoses of dermatomyositis (DM) associated with a double-positive anti-MDA5 and anti-aminoacyl-tRNA synthetase (anti-ARS) antibody presentation. Methods We retrospectively analyzed 1280 consecutive patients with idiopathic inflammatory myopathy (IIM). Individuals with anti-MDA5 and anti-ARS antibodies (anti-MDA5+/ARS+) were compared to anti-MDA5-/ARS+ and anti-MDA5+/ARS- control individuals based on clinical, pulmonary radiological characteristics, treatment, and follow-up information. Results Six individuals (0.47%) presented with anti-MDA5+/ARS+; of these, 2 (33.3%) were anti-PL-12+, 2 (33.3%) were anti-Jo-1+, 1 (16.7%) was anti-EJ+, and 1 (16.7%) was anti-PL-7+. Hallmark cutaneous manifestations, including Gottron’s sign (100%), heliotrope rash (50%), mechanic’s hand (66.7%), and skin ulcers (16.7%) were common. Anti-MDA5+/ARS+ patients tended to have higher ferritin levels (p = 0.038) than anti-MDA5-/ARS+ group, and higher CD4+ T-cell counts (p = 0.032) compared to the anti-MDA5+/ARS- group. Radiologically, NSIP with OP overlap was predominant (60%). Consolidation (60%), ground-glass attenuation (GGA) (80%), traction bronchiectasis (80%), and intralobular reticulation (100%) were common in anti-MDA5+/ARS+ individuals. All were diagnosed with ILD and 50% were categorized as RPILD. All patients received glucocorticoids combined with one or more immunosuppressants. Most (83.3%) had a good prognosis following treatment, but there was no difference in the survival rate between the three subgroups. Conclusion Presentation with anti-MDA5+/ARS+ DM was rare. The clinical and radiological characteristics of anti-MDA5+/ARS+ DM combined the features of anti-MDA5+ and anti-ARS+ individuals. Individuals with anti-MDA5+/ARS+ antibodies may respond well to glucocorticoid therapy; glucocorticoids combined with one or more immunosuppressants may be considered a basic treatment approach.